An Empirical Test of the Alternative Hypotheses of National and International Pricing of Risky Assets: Discussion - Scott, James H. (Journal of Finance, 1977)
James H. Scott, Jr., An Empirical Test of the Alternative Hypotheses of National and International Pricing of Risky Assets: Discussion, The Journal of Finance, Vol. 32, No. 2, Papers and Proceedings of the Thirty-Fifth Annual Meeting of the American Finance Association, Atlantic City, New Jersey, September 16-18, 1976 (May, 1977), pp. 515-517